The quadrate-metapterygoid fenestra of otophysan fishes, its development and homology - Ralf Britz; George M. T. Mattox; Kevin W. Conway (Vertebrate Zoology, 2023)
We compare the ontogeny of the hyopalatine arch in representatives of the Otophysi to shed light on the homology of the so-called quadrate-metapterygoid fenestra, QMF. Described initially as a character of characiforms (tetras and allies), presence of a QMF has also been reported for cobitid loaches and a handful of cyprinids among cypriniforms, as well as for a few clupeoids. In characiforms the QMF is either already present as an opening in the palatoquadrate cartilage in the earliest developmental stages we studied, or it forms later in the cartilage by resorption of chondrocytes. Some characiforms may lack a QMF during all stages of development. In cobitids the so-called QMF develops after the bones have ossified and forms mainly by resorption of bone tissue of quadrate and metapterygoid. Previous reports of a QMF in cyprinids are erroneous and the opening in this area forms by spatial separation of the quadrate and metapterygoid from the symplectic and not by the formation of a fenestra in the palatoquadrate cartilage. We suggest referring to this type as a quadrate-metapterygoid gap, QMG. Presence of a QMF in the palatoquadrate cartilage is a putative synapomorphy of characiforms. Development of a QMF by bone resorption in the ossified palatoquadrate is a putative synapomorphy of Cobitidae. A QMG is variously present and developed to different degrees in opsariichthyine and danionine cyprinids. A QMF is also present in several clupeoids and deserves further study.